PENERAPAN MODEL PEMBELAJARAN GROUP INVESTIGATION BERBANTUAN DIGITAL MIND MAP TERHADAP HASIL BELAJAR SISWA KELAS X IPA DI SMA - Lisanul Ulya Fatri; Siska Nerita; Annika Maizeli (Universitas Muhammadiyah Tapanuli Selatan, 2023)
The aim of this research is to determine student learning outcomes in the cognitive domain of class X Science by applying the Group Investigation learning model assisted by Digital Mind Map at SMAN 1 Pangkalan Koto Baru District. This type of research is included in the experimental research category which adopts a Randomized Control Group Posttest Only Design research design. The sampling technique was a total sampling technique because it only consisted of 2 classes, namely X IPA1 as the experimental class and X IPA2 as the control class. The research instrument used to measure the cognitive domain is in the form of a written test with multiple choice questions. The findings from this research show that the average score in the cognitive domain for the experimental class reached 86.2. In this class, 28 students or 93% succeeded in achieving graduation, while 2 students or 7% did not achieve graduation. On the other hand, the average score in the control class was 80.44, with 23 students or 79% who succeeded in achieving graduation and 6 students or 21% who did not succeed in achieving graduation. Based on the results of this research, it can be stated that the Group Investigation learning model assisted by Digital Mind Map is more effective in improving student learning outcomes in the cognitive domain in class X Science at SMAN 1 Pangkalan Koto Baru District.